2017
DOI: 10.22159/ijpps.2017v9i12.21084
|View full text |Cite
|
Sign up to set email alerts
|

Tualang Honey Attenuates Kainic Acid-Induced Oxidative Stress in Rat Cerebellum and Brainstem

Abstract: Objective: The present study examined the protective effect of tualang honey (TH) against kainic acid (KA)-induced oxidative stress in the cerebellum and brainstem of rats.Methods: Male Sprague-Dawley rats were randomly divided into four groups: Control, KA-treated, TH+KA-treated, and topiramate (TPM, an antiepileptic agent)+KA-treated groups. Rats were pretreated orally with drinking water, TH (1.0 g/kg body weight), or TPM (40 mg/kg body weight), respectively, five times at 12 h intervals. Saline or KA (15 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…In general, pure honey contains over 200 compounds, consisting mainly of carbohydrates (monosaccharides: glucose and fructose; disaccharides: sucrose and maltose), protein (amino acids and enzymes), minerals, vitamins (vitamin B6, riboflavin, niacin, and thiamine), phenolic compounds (flavonoids and phenolic acids), and volatile substance (responsible for the characteristic aroma of honey) [41][42][43][44][45][46]. In kainic acid-induced excitotoxicity animal model, pretreatment with honey significantly attenuated oxidative stress, neuroinflammation, and apoptosis in the cerebral cortex, cerebellum, and brainstem as well as progression of neuronal damage in the piriform cortex of kainic acid-induced rats [47][48][49]. Hence, honey confers its neuroprotection against the deleterious effect of kainic acid through its antioxidants and anti-inflammatory and antiapoptotic properties, thereby protecting brain from neuronal loss and neurodegeneration.…”
Section: Neuroprotective Activities Of Natural Products and Their Biomentioning
confidence: 99%
“…In general, pure honey contains over 200 compounds, consisting mainly of carbohydrates (monosaccharides: glucose and fructose; disaccharides: sucrose and maltose), protein (amino acids and enzymes), minerals, vitamins (vitamin B6, riboflavin, niacin, and thiamine), phenolic compounds (flavonoids and phenolic acids), and volatile substance (responsible for the characteristic aroma of honey) [41][42][43][44][45][46]. In kainic acid-induced excitotoxicity animal model, pretreatment with honey significantly attenuated oxidative stress, neuroinflammation, and apoptosis in the cerebral cortex, cerebellum, and brainstem as well as progression of neuronal damage in the piriform cortex of kainic acid-induced rats [47][48][49]. Hence, honey confers its neuroprotection against the deleterious effect of kainic acid through its antioxidants and anti-inflammatory and antiapoptotic properties, thereby protecting brain from neuronal loss and neurodegeneration.…”
Section: Neuroprotective Activities Of Natural Products and Their Biomentioning
confidence: 99%
“…Each major group was further randomly divided into three subgroups depending on the time of sacrifice (after 2 h, 24 h, and 48 h of KA administration; n = 6 rats per subgroup), with a total of 12 subgroups in each study. The groups are as follows: Group 1: the saline-treated group (control group) : rats received drinking water via oral gavage five times every 12 h. Group 2: the KA only-treated group: rats received drinking water via oral gavage five times every 12 h. Group 3: the tualang honey (TH) + KA-treated group: rats received Tualang honey (1.0 g/kg body weight; diluted in distilled water) via oral gavage five times every 12 h. The dosage of TH at 1.0 g/ body weight was selected based on the previous studies that demonstrated the protective effect of TH in a model of diabetic animals [ 37 ] and a model of menopause animals [ 38 ] as well as in our previous study [ 48 ]. Group 4: the topiramate (TPM) + KA-treated group : rats received TPM (40 mg/kg body weight; dissolved in 0.9 (w/v) NaCl solution with pH 8.0) via oral gavage five times every 12 h. The topiramate dosage was chosen based on other studies [ 50 – 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…Group 3: the tualang honey (TH) + KA-treated group: rats received Tualang honey (1.0 g/kg body weight; diluted in distilled water) via oral gavage five times every 12 h. The dosage of TH at 1.0 g/ body weight was selected based on the previous studies that demonstrated the protective effect of TH in a model of diabetic animals [ 37 ] and a model of menopause animals [ 38 ] as well as in our previous study [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alpha mangosteen, xanthone derived from this fruit, will attenuate brain inflammation that induced by peripheral lipopolysaccharide in rats [9]. As other traditional drug, one of the main properties of mangosteen is in reducing oxidative stress [10]. This present study was undertaken to explore the potential effects of mangosteen extract (ME) with the respect of astrogliosis, microglia activation, and malondialdehyde (MDA).…”
Section: Introductionmentioning
confidence: 99%